Elastomeric sandpaper replicas as model systems for investigating elasticity, roughness and associated drag in a marine biofilm flow cell. (15th December 2022) - Snowdon, Alexandra; An, Shi-Qi; Finnie, Alistair; Dale, Marie; Dennington, Simon; Longyear, Jennifer; Wharton, Julian; Stoodley, Paul
Abstract: Biofilm heterogeneity and adaptability complicates efforts to link biofilm structural and mechanical properties to frictional drag. As a result, rigid structures are typically used as the benchmark for studying biofilm-associated drag. Elastomeric sandpaper replicas were generated to be used as model systems for investigating the effect of roughness and elasticity on drag, over the Reynolds number range of approximately 2.0 × 10 4 to 5.2 × 10 4 Re using a marine biofilm flow cell. To control for roughness parameters and surface topography the replicas were created for sandpaper grit numbers: P40, P80 and P240 with average measured roughness (Sa ) of 108, 49 and 16 μm, respectively. Profilometry confirmed that there was no significant difference between the roughness of the rigid sandpaper sources and the material replicas. The marine biofilm flow cell was fitted with a clear lid, which allowed real-time visualisation of the replicas' surface topography using Optical Coherence Tomography. Pressure drop measurements, expressed as a friction coefficient, revealed that the elastomeric sandpaper replicas had a significantly higher associated drag, of up to 52%, when compared to the rigid counterparts. From statistical analysis it was confirmed that material mechanical properties, such as elasticity, and surface roughness both significantly affect drag. Elastic model systems can be used to enhance our understanding of biofilm physico-mechanics and their role in marine drag. Highlights: Created a novel method for creating an elastomeric biofilm model. Derived mesoscopic structural parameters in-situ using OCT. Roughness and elasticity had a significant shared and independent effect on drag. Elastomeric replicas increased drag by up to 52% compared to rigid structures. Importance of the effect of elasticity on drag is highlighted.